The handbook of mobile market research : tools and techniques for market researchers - Poynter, Ray.; Williams, Navin, 1972-; York, Sue, 1968- (Chichester, West Sussex, United Kingdom : John Wiley and Sons, Ltd., 2014)
The first book on the market that focuses on the area of mobile researchMore people have mobile phones than have computers or land lines and for several years researchers have understood that data collection needs to become mobile. Up until now, there were no systems available to do so, fuelled by incompatibilities between systems, lack of suitable systems, lack of understanding in terms of how to use mobile and too many organizations trying to put old fashioned surveys into the mobile world without confronting the changes that need to be made, e.g. shorter surveys. Ho.
Mobile Market Research -- Mobile Market Research. Overview of Mobile Market Research -- Mobile Research in Action -- The Technology of Mobile Market Research -- Qualitative and Quantitative Research -- Qualitative and Quantitative Research. Mobile Qualitative Research -- Mobile Forums and Online Focus Groups -- Mobile Diaries and Ethnography -- Mobile Quantitative Research -- Designing and Conducting Mobile Surveys -- The Methods and Applications of Mobile Market Research -- The Methods and Applications of Mobile Market Research. mCAPI : Mobile Computer Assisted Personal Interviewing -- mCATI : Mobile Computer Assisted Telephone Interviewing -- Mixed-Mode Research -- Utilizing Passive Data -- Panels, Lists, and Communities -- International Mobile Research -- Researching the Mobile Ecosystem, Ethics, and the Future -- Researching the Mobile Ecosystem, Ethics, and the Future. Researching the Mobile Ecosystem -- Ethics, Laws, and Guidelines -- Research-on-Research -- The Evolving Picture.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Marketing research; Mobile commerce; Mobile communication systems; Marketing -- Recherche; Commerce mobile; Radiocommunications mobiles; BUSINESS & ECONOMICS -- Marketing -- Research; Marketing research; Mobile commerce; Mobile communication systems